Expert System to Diagnose Dental Impaction Disease using Certainty Factor Method - Salu Zerwina; Yupianti Yupianti; Hari Aspriyono (Jurnal Media Computer Science, 2022)
The impaction of a tooth or pent-up tooth is the condition of a tooth trapped inside the gums. In most case, dental impact occurs in the wisdom teeth of adults. Dental impaction makes a person more susceptible to tooth decay and gum disease But the number of people who are lay about dental impaction disease, it is necessary to have a system that can be accessed online to help patients or the public to be able to consult independently. This expert system is designed using the PHP Programming Language and MySQL Databse.